Management duration controls the synergistic effect of tillage, cover crop, and nitrogen rate on cotton yield and yield stability - Nouri, Amin; Lee, Jaehoon; Yoder, Daniel C.; Jagadamma, Sindhu; Walker, Forbes R.; Yin, Xinhua; Arelli, Prakash (Agriculture, ecosystems & environment, 2020)
•Management duration controls the response of cotton yield and yield stability to tillage, bio-covers, and N rate management.•Long-term interaction between legume covers and no-tillage increased yield stability in adverse environmental conditions.•Long-term incorporation of legume species, especially hairy vetch further enhanced the yield outcome from no-tillage system. Resilient agroecosystems are foundational for stable and profitable food, feed, and fiber production in the face of increasing climatic perturbations and environmental stresses. Enhanced soil and environmental benefits of cover crops applied to conservation tillage systems has been well documented. However, little is known about the timespan for interactions of no tillage and cover crops to achieve enhanced yield and yield stability while lowering N fertilization. Using a long-term continuous cotton experiment in southeastern USA, we analyzed yield data collected from 1986 to 2018 from 32 management systems to identify how management duration controls the synergistic effect of applied mineral N rates (0, 34, 67, and 101 kg ha−1), cover crops (no cover [NC], hairy vetch [HV], crimson clover [CC], and winter wheat [WW]), and tillage practices (no tillage [NT] and conventional tillage [CT]) on cotton yield and yield stability. Yield stability was analyzed using Finlay—Wilkinson regression model, Wricke’s Ecovalance, and coefficient of variation, and a mixed model approach was used to compare the yield and yield stability within three time phases (1−10 years, 11–20 years, and 21−33 years) at the 95% confidence level. During the initial 10 yr period (phase 1) CT resulted in greater cotton yield (7%) and yield stability than NT. However, in phase 2 (11–20 years) and phase 3 (21−33 years) NT led to greater yield (7%) and yield stability for almost all cover crop × N interactions, except for zero N following NC and WW. Increased N during the initial phase reduced both yield and yield stability under legume cover crops. During phases 2 and 3, however, the higher N rates (67 and 101 kg N ha−1) increased cotton yield, although management systems with 0 and 101 kg N ha−1 showed the largest temporal yield variability. Legume cover crops increased yield and yield stability under low N rates. The maximum combined yield and yield stability benefit was obtained from HV cover on NT with additional application of 34 kg N ha−1. Our results suggest that after the initial phase NT delivers the most consistent yield benefits while enhancing yield stability against unfavorable environmental conditions. Long-term integration of legume cover crops (particularly HV) to NT systems was effective in maintaining high yield and increasing yield stability while lowering N rates.